Immediate Implant Loading : Current Concepts: A Case Report - Munjal, Seema; Munjal, Sumit (Journal of Orofacial Research, 2011)
With the advent of immediate single stage implant placement and immediate prosthesis fabrication, the edentulous patients can today walk out with “Teeth in a day”. Moreover, the refinement of clinical protocols, the application of sound biomechanical principles, improvements in implant design, and the development of new implant surfaces have resulted in the increased use of this procedure. The primary disadvantage, however is the risk of implant failure or greater crestal boneloss around the healing implants. The majority of clinical reports, nonetheless reveal similar survival rates between immediately loaded and two-stage unloaded healing approaches. This review article throws a light on advantages, disadvantages and success criteria for immediate implant loading. A case with single tooth immediate implant rehabilitation is reported.